DEVELOPMENT OF MATHEMATICAL LEARNING DEVICES ON TRIGONOMETRY MATERIAL WITH THE PEER TUTORING METHOD - Nurelyati; Zetriuslita (UIR PRESS, 2023)
This study aims to produce mathematics learning tools in the form of syllabi, learning implementation plans (RPP), and student worksheets (LKPD) using the peer tutoring method in senior high schools that are tested for validity. The development of learning tools in this study uses the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, and Evaluation. However, due to Covid-19 constraints, researchers can only develop the ADDIE model up to the Analysis, Design, and Development stages. The data collection instrument in this study used syllabus validation sheets, lesson plans validation sheets, and worksheet validation sheets. The data collection technique used was validation data from 2 Lecturers of FKIP Mathematics at Riau Islamic University and 2 Mathematics Subject Teachers at SMA PGRI Pekanbaru. The data analysis technique used is a descriptive statistical analysis which describes the data that has been collected and will be tested for its validity. From the results of the validity test, it was obtained that the syllabus validation results were 93.02% with very valid information, the RPP validation results were 96.36% with very valid information, and the LKPD validation results were 95.80% with very valid